2007
DOI: 10.1068/p5845
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Optic Flow Speed Discrimination While Walking: Contextual Tuning of Visual Coding

Abstract: We tested the hypothesis that long-term adaptation to the normal contingencies between walking and its multisensory consequences (including optic flow) leads to enhanced discrimination of appropriate visual speeds during self-motion. In experiments 1 (task 1) and 2 a two-interval forced-choice procedure was used to compare the perceived speed of a simulated visual flow field viewed while walking with the perceived speed of a flow field viewed while standing. Both experiments demonstrated subtractive reductions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 35 publications
3
55
0
1
Order By: Relevance
“…Similarly, evidence that the perceptual discrimination function for visual speed is altered during self-motion, so that speed sensitivity is tuned to expected visual speeds (Durgin & Gigone, 2007), is not undermined by the knowledge that the spatial scaling of VR is known to be problematic. Discrimination is discrimination.…”
Section: P Smentioning
confidence: 99%
“…Similarly, evidence that the perceptual discrimination function for visual speed is altered during self-motion, so that speed sensitivity is tuned to expected visual speeds (Durgin & Gigone, 2007), is not undermined by the knowledge that the spatial scaling of VR is known to be problematic. Discrimination is discrimination.…”
Section: P Smentioning
confidence: 99%
“…For example, Mittelstaedt and Mittelstaedt (2001) showed that for all distances, distance estimation depended on walking velocity. However, Durgin and Gigone (2007) argued that locomotor speed is controlled by stride frequency and that people tend to judge themselves as moving faster if they took shorter and more frequent steps. Furthermore, while there is good evidence that rhythmic activity can improve time-keeping, Durgin et al (2009) also showed that distance estimation is more precise than timing estimation, leading to the conclusion that timing is not a mechanism for distance estimation but rather distance itself or step length is the key component.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is good evidence to suggest that other factors apart from time can contribute to successful non-visual distance estimation. Such factors include step frequency (Durgin, Akagi, Gallistel, & Haiken, 2009;Durgin & Gigone, 2007), walking velocity (Mittelstaedt & Mittelstaedt, 2001) and stored velocity profiles (Berthoz, Israël, Georges-François, Grasso, & Tsuzuku, 1995). As well as locomotor information, different cognitive factors, including task demands (Ellard & Shaughnessy, 2003) and confidence (Philbeck, Woods, Arthur, & Todd, 2008) may also play a role.…”
Section: Introductionmentioning
confidence: 99%
“…The reductions in perceived display speed produced by treadmill walking compared with stationary viewing were the same regardless of whether the stationary subjects viewed smooth or jittering optic flow. Furthermore, Durgin and colleagues (Durgin and Gigone 2007;Durgin et al 2005) also showed that reductions in the visually perceived display speed during treadmill walking (compared with stationary viewing) are proportional to physical walking speed, with the greatest reductions occurring for faster treadmill belt speeds and speeds closest to normal walking speeds. Barlow's (1990) theory does not explicitly state whether redundant sensory information generates reductions in visually perceived object motion, visually perceived self-motion, or both.…”
Section: Redundant Multisensory Information During Treadmill Walkingmentioning
confidence: 99%
“…A number of seated (Li et al 2009;Yeung and Li 2013) and treadmill walking studies (Durgin and Gigone 2007;Durgin et al 2005) have found reductions in visually perceived object motion during redundant multisensory situations. These previous findings appear to be generally consistent with Barlow's inhibition theory, which asserts that: (i) there is a reduction in the salience of retinal motion during positively correlated (as opposed to uncorrelated or negatively correlated) multisensory events because these situations provide redundant information about self-motion; and (ii) redundant retinal motion signals are suppressed by nonvisual signals to minimise their salience.…”
Section: Redundant Multisensory Information During Treadmill Walkingmentioning
confidence: 99%